2008
DOI: 10.1002/sia.2618
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic investigations of the role of Ge in modifying the Si to SiC conversion process

Abstract: The influence of Ge on the conversion process of Si to SiC was studied by depositing Ge and C on Si(111) followed by a stepwise annealing procedure. After the annealing step, the carbon deposited on the surface was completely converted into SiC. In the case of Ge predeposition, the SiC amount detected by XPS, AES and ellipsometry was lower compared to the reference sample in which no Ge was predeposited on the Si(111) surface. Therefore, Ge lowers the probability of SiC formation in the early stages. During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…An additional corroboration of the hypothesis of compressive in-plane strain is the recently obtained TO phonon positions of 3C-SiC(111) formed on on-axis Si(111) substrates around 800 cm −1 . [49] Further experimental evidence indicating a compressive strain in the carbonized layer is the TO phonon position at 800 cm −1 at the 3C-SiC(111)/Si(111) interface of epitaxial layers grown by SSMBE on carbonized Si(111) substrates using the same approach as in this investigation obtained by infrared spectroscopic ellipsometry. [50] Normally, due to the inherent differences of the thermal expansion, coefficients between 3C-SiC and Si the SiC layers are tensile stressed.…”
Section: Resultsmentioning
confidence: 94%
“…An additional corroboration of the hypothesis of compressive in-plane strain is the recently obtained TO phonon positions of 3C-SiC(111) formed on on-axis Si(111) substrates around 800 cm −1 . [49] Further experimental evidence indicating a compressive strain in the carbonized layer is the TO phonon position at 800 cm −1 at the 3C-SiC(111)/Si(111) interface of epitaxial layers grown by SSMBE on carbonized Si(111) substrates using the same approach as in this investigation obtained by infrared spectroscopic ellipsometry. [50] Normally, due to the inherent differences of the thermal expansion, coefficients between 3C-SiC and Si the SiC layers are tensile stressed.…”
Section: Resultsmentioning
confidence: 94%
“…AlN layers were grown on SiC substrates with various predeposition of Ge amount at the pseudo-substrate SiC/Si (111) interface. Ge was deposited at the Si interface prior to the SiC epitaxial growth at low temperature using SSMBE [22], this method is important to eliminate the defects and to improve the epilayer quality [23]; it was confirmed that the Ge incorporation before the carbonization process is an effective way to improve crystalline quality of the SiC grown layer [24,25], reduce the stress in the upper-layer [26,27] and affects in an important way the layers' structure [28,29]. It is possible to identify the present samples by the Ge pre-deposited amount-2, 1 and 0.5 ML.…”
Section: Article In Pressmentioning
confidence: 88%
“…For Si(111) substrates a positive effect of Ge on the surface morphology of the SiC layers was proven which is related to modified nucleation conditions at the carbonization stage, i.e. the conversion of Si(111) into 3C-SiC(111), prior to epitaxial growth of 3C-SiC [7,8]. The different behaviour of Si(100) substrates concerning the stress relaxation of the 3C-SiC layers by Ge pre-treatment arose the question whether or not this is caused by differrences in the conversion mechanism compared to Si(111) substrates.…”
mentioning
confidence: 98%